(untitled) (Minerva, 2017)
French Enlightenment received some important characteristics from the Humanistic culture of the previous centuries. Like their predecessors, many intellectuals of the eighteenth century were familiar with the most important works of the ancient authors. During this period, the roman writer Marcus Fabius Quintilian was popular in academic circles, and his teachings were used by some of the most important scholars.